PENGARUH KONSENTRASI LARUTAN GULA TERHADAP SEDIAAN SIRUP SELEDRI (APIUM GRAVEOLENS L.) - Adita Silvia Fitriana (Viva Medika, 2018)
Abstract Celery plants (Apium graveolens L.) have long been used as ingredients of traditional medicine as antihypertensive by the people of Indonesia. This study aims to determine the effect of variations in the addition of celery leaf extract on the manufacture of functional food in the form of syrup from celery leaf extract (Apium graveolens L.) on organoleptic assessment and the quality of syrup preparations. This study used a Completely Randomized Design (CRD) consisting of 5 types of treatment and each treatment was repeated 3 times. Variation of addition of celery leaf extract as follows: (M0) = 0% (control), (M1) = 0.33% (0.55 g), (M2) = 0.39% (0.65 g), (M3 ) = 0.51% (0.85 g) and (M4) = 0.6% (1 g). The results showed that celery leaf extract had antioxidant activity with IC50 values ​​of 98.24 µg / mL and positive (+) containing flavonoids. The addition of celery leaf extract to syrup has a very significant effect on organoleptics (aroma and taste), 7th day pH and viscosity, and all homogeneous syrups. The most preferred treatment panelist was treatment M1 (0.33%) with a scoring score of 4.03 (likes) and a taste of 3.93 (likes) and according to SNI. While the panelists preferred the treatment of M4 (0.6%) with a scoring score of 3.24 (rather like) and flavor of 2.87 (rather like) but according to SNI. The fewer additions of celery leaf extract, the syrup is increasingly preferred by panelists. Keywords: celery, formulation, syrup